THE IMPLEMENTATION OF THE FUNCTION OF THE LAND OFFICE IN RESOLVING LAND DISPUTES THROUGH MEDIATION - Chilsy indiyarti.S; Syahruddin Nawi; Ilham Abbas (Meraja journal, 2021)
[Full Paper] to pdf Copyright (c) 2021 Meraja journal